Ability of different assay platforms to measure renal biomarker concentrations during ischaemia-reperfusion acute kidney injury in dogs. (March 2021) - Davis, Jennifer; Rossi, Gabriele; Miller, David W.; Cianciolo, Rachel E.; Raisis, Anthea L.
Abstract: Several protein biomarkers have been shown to be useful for the early diagnosis of acute kidney injury (AKI) in animals and people. Multiplex assays for measurement of a panel of renal biomarkers in canine samples have recently become available. This study compared the use of two such assays, versus previously validated ELISAs, to measure five biomarkers in canine samples during ischaemia-reperfusion (IR) AKI. Blood and urine was collected from six male anaesthetised greyhounds that underwent 1-h of renal ischaemia (severe hypotension induced by acute haemorrhage) and 2-h of reperfusion (intravenous fluid resuscitation). Histology confirmed presence of acute tubular injury at 2 h of reperfusion. Concentrations of clusterin, cystatin C, kidney-injury molecule 1 (KIM-1), monocyte chemoattractant protein 1, and neutrophil gelatinase-associated lipocalin (NGAL) at baseline and following IR, measured by two different multiplex assays and previously-validated single analyte immunoassays, were compared. Only NGAL was significantly elevated following IR with all assays investigated. Whether concentrations of the other four biomarkers were significantly increased following IR depended on the assay used. Concentrations of cystatin C and KIM-1 measured with the multiplex assays were of a vast magnitude lower than those measured with the corresponding single analyte ELISAs. We conclude that further validation is required before these assays can reliably be used to measure AKI biomarkers in canine samples. Highlights: Renal biomarkers were measured in canine samples before and 2 h following ischaemic injury. Measurements by multiplex assays were compared to those from enzyme-linked immunoassays. Neutrophil gelatinase-associated lipocalin was significantly elevated according to all assays. Cystatin C and kidney injury molecule 1 were poorly detected by one multiplex assay. Further validation of multiplex immunoassays for renal biomarkers in canine samples is required.